Phytochemical Examination, GC-MS Analysis, and Antibacterial Activity of Methanol Extract of Dadap Leaves (Erythrina variegata L.) Against Staphylococcus aureus and Escherichia coli Bacteria using Disc Diffusion Method - Yulia Theodora Situmorang; Halimatussakdiah Halimatussakdiah; Ulil Amna; Vivi Mardina (UNIVERSITAS SEBELAS MARET (UNS), 2026)
This study examines the antibacterial activity of a methanol extract from the leaves of Dadap (Erythrina variegata L.) against Staphylococcus aureus and Escherichia coli. Bacterial infections are a major health issue in Indonesia, so the development of plant-based natural medicines is being pursued. The Dadap plant has the potential to treat bacterial infections. This study aims to identify the types of secondary metabolites in the methanol extract of Dadap leaves, analyze the active compounds using Gas Chromatography-Mass Spectroscopy (GC-MS), and evaluate their antibacterial activity. Extraction was performed by maceration with methanol, and antibacterial testing was conducted by disk diffusion on Mueller-Hinton Agar with extract concentrations of 5, 10, 20, and 40% (w/v). The extracts were diluted in sterile distilled water. The results exhibited antibacterial activity against S. aureus and E. coli, with inhibition zones of 14 mm (strong) and 8.8 mm (moderate) at a 40% concentration, respectively. These activities might be linked to the active compounds found in the Dadap leaves extract using phytochemical and GC-MS analysis. The phytochemical analysis showed that the E. variegata L. leaf extract contains alkaloids, steroids, terpenoids, saponins, flavonoids, phenols, and tannins. Furthermore, the GC-MS chromatogram identified 11 compounds, including 7 with antibacterial activity, such as neophytadiene, 3,7,11,15-tetramethyl-2-hexadecen-1-ol, hexadecanoic acid, methyl ester, n-hexadecanoic acid, phytol, methyl stearate, and stigmasterol. Overall, the crude extract of Dadap leaves showed a potential candidate for development as an antibiotic.